Pharmacokinetics, metabolism and serum concentrations of progestins used in contraception - Bick, Alexis J.; Louw-du Toit, Renate; Skosana, Salndave B.; Africander, Donita; Hapgood, Janet P. (Pharmacology & therapeutics (Oxford), 2021)
Many different forms of hormonal contraception are used by millions of women worldwide. These contraceptives differ in the dose and type of synthetic progestogenic compound (progestin) used, as well as the route of administration and whether or not they contain estrogenic compounds. There is an increasing awareness that different forms of contraception and different progestins have different side-effect profiles, in particular their cardiovascular effects, effects on reproductive cancers and susceptibility to infectious diseases. There is a need to develop new methods to suit different needs and with minimal risks, especially in under-resourced areas. This requires a better understanding of the pharmacokinetics, metabolism, serum and tissue concentrations of progestins used in contraception as well as the biological activities of progestins and their metabolites via steroid receptors. Here we review the current knowledge on these topics and identify the research gaps. We show that there is a paucity of research on most of these topics for most progestins. We find that major impediments to clear conclusions on these topics include a lack of standardized methodologies, comparisons between non-parallel clinical studies and variability of data on serum concentrations between and within studies. The latter is most likely due, at least in part, to differences in intrinsic characteristics of participants. The review highlights the importance of insight on these topics in order to provide the best contraceptive options to women with minimal risks. [Display omitted]